THE EFFECT OF INTRINSIC MOTIVATION AND ATTITUDE TO FULFILLMENT OF IMMUNIZATION DURING PANDEMIC - Devika Aulia; Ivon Diah Wittiarika; Irwanto Irwanto (UNIVERSITAS AIRLANGGA, 2022)
Background: The milestone in protecting the nation's next-generation from disease is to provide basic immunization as natural protection against specific infections. Covid-19 has hit Indonesia since early 2020, disrupting all aspects of life, especially health, which is manifested in a decrease in basic immunization coverage. The purpose of this study was to determine the influence between intrinsic motivation and mother's attitude towards the fulfillment of basic immunization during the Covid-19 pandemic. Methods: The research method used is analytic observation using the Spearman test with a p-value <0.05. Respondents of this study were mothers with children aged 0-12 months at Puskesmas Jatibening Baru, Bekasi, as many as 37 respondents with the total sampling method. The research instrument was an online questionnaire with variables of intrinsic motivation and mother's attitude. Results: Based on research analysis using the Spearman test, the p-value = 0.376 and the Spearman correlation coefficient of 0.150 to see the effect between mother's intrinsic motivation and the status of basic immunization fulfillment during the Covid-19 pandemic. The results of the p-value to see the effect of mother's attitude with basic immunization fulfillment status during the Covid-19 pandemic was 0.182, and the Spearman correlation coefficient was 0.224. Conclusion: There is no effect between intrinsic motivation and mother's attitude towards the fulfillment of basic immunization during the Covid-19 pandemic. Keywords : Attitudes; Basic Immunization; Covid-19; Intrinsic Motivation